Preparation method of spherical aluminum oxide-zinc oxide composite powder
The preparation of spherical alumina-zinc oxide powders through high-temperature hydrothermal method and spray granulation technology has solved the problem of insufficient dispersion and compatibility of existing composite powders, and significantly improved its performance in thermally conductive materials.
Patent Information
- Application Number
- CN202411837645.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The existing alumina-zinc oxide composite powders are insufficient in dispersion and compatibility in organic matrix, resulting in poor performance in thermally conductive materials.
Alumina-zinc oxide precursor was generated by high-temperature hydrothermal method, and a spherical precursor was made by spray granulation technology. Then, high-temperature sintering was performed in air or oxygen atmosphere, and spherical alumina-zinc oxide powder was prepared in combination with the bonding effect of yttrium salt.
The sphericalization and smooth surface of the alumina-zinc oxide composite powder are achieved, which significantly improves its dispersion and compatibility in the composite material and enhances thermal conductivity.
Smart Images

Figure CN119660776A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of inorganic non-metallic powder preparation, and specifically relates to a method for preparing spherical aluminum oxide-zinc oxide composite powder. Background Art
[0002] Zinc oxide is an important inorganic material with a variety of crystal structures, including hexagonal wurtzite structure, cubic sphalerite structure and sodium chloride octahedral structure. Its hardness is about 4.5, and it is a relatively soft material with high breakdown voltage, excellent piezoelectric properties, good thermal stability and thermal conductivity. The room temperature thermal conductivity is about 30W / (m·K), so it has been widely used in thermal conductive fillers for polymers.
[0003] Alumina is a high-hardness inorganic compound with excellent electrical insulation and high thermal conductivity, with a thermal conductivity of about 36W / (m·K). Alumina is not only a commonly used electrical insulation thermal conductive particle, but also has a relatively low price, so it is widely used in thermal conductive materials. Alumina also has a high melting point and good high temperature resistance, and can remain stable under high temperature conditions, so it has also been widely used in thermal conductive fillers for polymers.
[0004] In recent years, many studies have been devoted to the preparation of inorganic composite materials with good dispersibility and excellent compatibility. Invention patent CN118027709A discloses a method for preparing an alumina filler and the application of an alumina filler in a two-component silicone potting compound. The method mixes alumina and zinc oxide into a silane coupling agent alcohol solution, and then performs ball milling modification to prepare zinc oxide-coated alumina powder to enhance its compatibility in silicone polymer materials. However, due to the use of ball milling modification technology, zinc oxide cannot be completely coated on the surface of alumina, resulting in general enhancement of its dispersibility and compatibility. Invention patent CN112876849A discloses a method for preparing a composite thermal conductive interface material thermal conductive silicone grease. This method directly compounds aluminum oxide, zinc oxide and other powders to make the thermal conductive silicone grease have good electrical insulation and high temperature stability. However, since the powders are simply compounded, there are gaps between the particles, and fine-grained aluminum oxide and fine-grained zinc oxide are easy to agglomerate and difficult to disperse in a polymer matrix material, resulting in poor compatibility between them and the polymer. Summary of the invention
[0005] Based on the problems described in the background technology, the purpose of the present invention is to provide a method for preparing spherical aluminum oxide-zinc oxide composite powder, thereby realizing the preparation of aluminum oxide-zinc oxide composite powder; the prepared spherical aluminum oxide-zinc oxide powder has high sphericity, a smooth surface, and no voids, and has good dispersibility and excellent compatibility in an organic matrix.
[0006] The present invention provides a method for preparing spherical aluminum oxide-zinc oxide composite powder, and the specific formation process and principle thereof are as follows: (1) First, in a reactor, a zinc source and an alkali source react under high temperature hydrothermal conditions to generate a zinc oxide precursor. At the same time, an aluminum source and an alkali source also undergo a hydrothermal reaction under the same conditions to generate an aluminum oxide precursor. Under the action of a peptizing agent, the aluminum oxide precursor is converted into aluminum sol, which is uniformly adsorbed on the surface of the zinc oxide precursor. (2) Subsequently, the aluminum oxide-zinc oxide precursor slurry is made into spherical aluminum oxide-zinc oxide precursor particles by spray granulation technology. Then, the spherical precursor is subjected to high-temperature sintering treatment in a muffle furnace under air or oxygen atmosphere to obtain the final spherical aluminum oxide-zinc oxide powder. (3) During the high-temperature sintering process, the yttrium salt melts under high temperature conditions to form a liquid substance, which has a strong bonding effect and effectively prevents the spherical aluminum oxide-zinc oxide particles from breaking, thereby maintaining good sphericity and ensuring the quality of the final product. The experimental results show that the present invention successfully prepares spherical aluminum oxide-zinc oxide composite powders with good sphericity and stability, verifying the feasibility and effectiveness of the method.
[0007] The present invention provides a method for preparing spherical aluminum oxide-zinc oxide, comprising the following steps: (1) Preparing a spherical aluminum oxide-zinc oxide precursor: a zinc source, an aluminum source, an alkali source, and distilled water are transferred into a stainless steel reactor lined with polytetrafluoroethylene, heated at 300 to 500° C. for reaction for 24 to 72 hours, and cooled naturally to room temperature to obtain an aluminum oxide-zinc oxide precursor slurry, and the aluminum oxide-zinc oxide precursor slurry, yttrium salt, and peptizing agent are placed in a spray dryer for granulation to obtain a spherical aluminum oxide-zinc oxide precursor; the air inlet temperature of the spray dryer is 200 to 350° C., the fan frequency is 20 to 40 Hz, the needle passing time is 1 to 5 seconds, and the peristaltic pump speed is 10 to 30 r / min; (2) Preparation of spherical alumina-zinc oxide powder: The spherical alumina-zinc oxide precursor prepared in the above (1) is added to a crucible, and the crucible is placed in an atmosphere furnace and calcined in air or oxygen at a calcination temperature of 800-1300°C for 1-12 hours. After the sintered body is naturally cooled to room temperature, it is placed in a planetary ball mill at a rotation speed of 100-300 r / min and ball-milled for 5-90 minutes to obtain spherical alumina-zinc oxide powder.
[0007] In the step (1), the mass ratio of the zinc source, the aluminum source, the alkali source, the distilled water, the peptizing agent and the yttrium salt is 3-10:1-3:3-10:10-200:1-10:0.1-5.
[0008] In the step (1), the zinc source is one or more of zinc chloride, zinc sulfate, zinc nitrate and zinc carbonate.
[0009] In the step (1), the aluminum source is one or more of aluminum chloride, aluminum nitrate, aluminum sulfate, sodium aluminum acid, and potassium aluminum acid.
[0010] In the step (1), the alkali source is one or more of ammonia water, cyanuric chloride, melamine, urea and imidourea.
[0011] In the step (1), the yttrium salt is one or more of yttrium chloride, yttrium nitrate, and yttrium acetate.
[0012] In the step (1), the peptizing agent is one or more of acetic acid and citric acid.
[0013] In the step (2), calcination is carried out in air or oxygen, and the calcination temperature is 800-1300°C.
[0014] The present invention has the following technical advantages: (1) The present invention successfully prepares aluminum oxide-zinc oxide composite powders and realizes the sphericity of aluminum oxide-zinc oxide. The spherical aluminum oxide-zinc oxide is firmly bonded, has high sphericity and is not easy to break; (2) The surface of the spherical aluminum oxide-zinc oxide powder prepared by the present invention is smooth and void-free, so that it has good dispersibility and compatibility, and significantly improves the filling performance and thermal conductivity of the spherical aluminum oxide-zinc oxide powder in the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is the SEM image of the spherical aluminum oxide-zinc oxide composite powder prepared in Example 1.
[0016] Figure 2 This is the SEM image of the product prepared in Comparative Example 1.
[0017] Figure 3 This is the SEM image of the product prepared in Comparative Example 2.
[0018] Figure 4 This is the SEM image of the product prepared in Comparative Example 3. DETAILED DESCRIPTION
[0019] The embodiments described below specifically illustrate the above contents of the present invention, and particularly illustrate that, based on the principles of the present invention, several adjustments and improvements may be made, and these adjustments and improvements are also considered to be within the protection scope of the embodiments of the present invention.
[0020] Example 1 (1) Preparation of spherical aluminum oxide-zinc oxide precursor: 30 g zinc chloride, 10 g aluminum chloride, 30 g ammonia water, and 100 g distilled water were transferred into a stainless steel reactor lined with polytetrafluoroethylene, heated at 300° C. for 24 h, and naturally cooled to room temperature to obtain an aluminum oxide-zinc oxide precursor slurry. The aluminum oxide-zinc oxide precursor slurry, 10 g acetic acid, and 1 g yttrium chloride were placed in a spray dryer for granulation to obtain a spherical aluminum oxide-zinc oxide precursor; the air inlet temperature of the spray dryer was 200° C., the fan frequency was 20 Hz, the needle passing time was 1 s, and the peristaltic pump speed was 10 r / min (the mass ratio of zinc chloride, aluminum chloride, ammonia water, distilled water, acetic acid, and yttrium chloride was 30:10:30:100:10:1); (2) Preparation of spherical aluminum oxide-zinc oxide powder: 500 g of spherical aluminum oxide-zinc oxide precursor was added to a crucible, and the crucible was placed in an atmosphere furnace and calcined under air or oxygen at a calcination temperature of 800° C. for 1 h. After the sintered body was naturally cooled to room temperature, it was placed in a planetary ball mill at a speed of 100 r / min and ball milled for 5 min to obtain spherical aluminum oxide-zinc oxide powder;
[0021] Example 2 (1) Preparation of spherical aluminum oxide-zinc oxide precursor: 60 g of zinc sulfate, 20 g of aluminum nitrate, 60 g of ammonia water, and 300 g of distilled water were transferred into a stainless steel reactor lined with polytetrafluoroethylene, heated at 400° C. for reaction for 48 h, and naturally cooled to room temperature to obtain an aluminum oxide-zinc oxide precursor slurry. The aluminum oxide-zinc oxide precursor slurry, 30 g of acetic acid, and 3 g of yttrium nitrate were placed in a spray dryer for granulation to obtain a spherical aluminum oxide-zinc oxide precursor; the air inlet temperature of the spray dryer was 280° C., the fan frequency was 30 Hz, the needle passing time was 3 s, and the peristaltic pump speed was 20 r / min (the mass ratio of zinc sulfate, aluminum nitrate, ammonia water, distilled water, acetic acid, and yttrium nitrate was 60:20:60:300:30:3); (2) Preparation of spherical aluminum oxide-zinc oxide powder: 800 g of spherical aluminum oxide-zinc oxide precursor was added to a crucible, and the crucible was placed in an atmosphere furnace and calcined under air or oxygen at a calcination temperature of 1000° C. for 6 h. After the sintered body was naturally cooled to room temperature, it was placed in a planetary ball mill at a speed of 200 r / min and ball milled for 30 min to obtain spherical aluminum oxide-zinc oxide powder;
[0022] Example 3 (1) Preparation of spherical aluminum oxide-zinc oxide precursor: 100 g zinc carbonate, 30 g aluminum sulfate, 100 g urea, and 2000 g distilled water were transferred into a polytetrafluoroethylene-lined stainless steel reactor, heated at 500° C. for reaction for 72 h, and naturally cooled to room temperature to obtain an aluminum oxide-zinc oxide precursor slurry. The aluminum oxide-zinc oxide precursor slurry, 100 g citric acid, and 50 g yttrium acetate were placed in a spray dryer for granulation to obtain a spherical aluminum oxide-zinc oxide precursor; the air inlet temperature of the spray dryer was 350° C., the fan frequency was 40 Hz, the needle passing time was 5 s, and the peristaltic pump speed was 30 r / min (the mass ratio of zinc carbonate, aluminum sulfate, urea, distilled water, citric acid, and yttrium acetate was 100:30:100:2000:100:50); (2) Preparation of spherical aluminum oxide-zinc oxide powder: 1500 g of spherical aluminum oxide-zinc oxide precursor was added to a crucible, and the crucible was placed in an atmosphere furnace and calcined under air or oxygen at a calcination temperature of 1300° C. for 12 h. After the sintered body was naturally cooled to room temperature, it was placed in a planetary ball mill at a speed of 300 r / min and ball milled for 90 min to obtain spherical aluminum oxide-zinc oxide powder;
[0023] Comparative Example 1 The aluminum oxide-zinc oxide precursor slurry in step (1) of Example 1 is replaced with a slurry mixed with 5 μm irregular aluminum oxide, 5 μm irregular zinc oxide, acetic acid, yttrium chloride, and distilled water. The mass of each component in the slurry is the same as in Example 1, and the subsequent steps are the same as in Example 1.
[0024] Comparative Example 2 The method and steps of Example 1 are basically repeated, except that acetic acid is not added in step (1).
[0030] Comparative Example 3 The method and steps of Example 1 are basically repeated, except that yttrium chloride is not added in step (1).
[0025] The performance test methods and standards are as follows: Maximum filling test: 60g of 500cP vinyl silicone oil, 1.52g of hydrogenated silicone oil, 0.2g of ethynyl cyclohexanol, and 0.3g of 3000ppm chloroplatinic acid were mixed evenly, and a certain amount of powder fillers of the embodiments of the present invention and the comparative example were added. After preliminary dispersion, the mixture was placed in a vacuum stirring degassing machine with a speed of 800r / min set, stirred for 4min, and then calendered and shaped into a cured sheet with a thickness of 2mm using a molding machine. The cured sheet was placed in an oven at 120°C and dried for 1h. The cured sheet was taken out and naturally cooled to room temperature. The maximum filling was reached if the cured sheet did not fall off and the surface did not crack.
[0026] Table 1: Maximum filling number of spherical aluminum oxide-zinc oxide composite powders prepared in each case serial number Maximum number of fillings Example 1 1200 copies Example 2 1100 copies Example 3 1000 copies Comparative Example 1 400 copies Comparative Example 2 400 copies Comparative Example 3 400 copies
[0027] From the attached figure and the data in Table 1, we can see that: (1) Scanning electron microscopy images ( Figure 1-4 ) analysis, comparative example 1 ( Figure 2 ) was used to carry out spherical granulation experiments with irregular aluminum oxide and irregular zinc oxide, and the particle morphology was irregular agglomerates; Comparative Example 2 ( Figure 3 ) was not added with a peptizing agent to carry out a spherical granulation experiment, and the particle morphology was an agglomerate of irregular shape; Comparative Example 3 ( Figure 4 ) was not added with yttrium salt to carry out spherical granulation experiment, and the particle morphology was irregular agglomerates; while the spherical aluminum oxide-zinc oxide composite powder ( Figure 1 ), its morphology is spherical with smooth surface and no pores. (2) According to the analysis of the maximum filling ratio of the spherical alumina-zinc oxide composite powder prepared in each example (Table 1), compared with comparative examples 1 to 3, the spherical alumina-zinc oxide composite powder embodiments 1 to 3 of the present invention are more excellent in dispersion performance, and the filling ratio in 500 cP vinyl silicone oil can be increased by 150 to 200%, indicating that the spherical alumina-zinc oxide composite powder greatly improves the dispersion performance of alumina / zinc oxide and its compatibility with silicone, and greatly improves the thermal conductivity of the spherical alumina-zinc oxide composite material.
[0028] As can be seen from the above examples, the present invention successfully prepares spherical aluminum oxide-zinc oxide powder, solving the disadvantage of poor dispersion performance of aluminum oxide / zinc oxide in the prior art. In addition, the method is simple, fast, green and environmentally friendly, can be mass-produced, and is easy to promote.
[0029] The above description is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, all equivalent changes or modifications made according to the structure, characteristics and principles described in the scope of the patent application of the present invention are included in the protection scope of the present invention.
Claims
1. A method for preparing spherical aluminum oxide-zinc oxide composite powder, characterized in that: The following steps are involved: (1) Preparing a spherical aluminum oxide-zinc oxide precursor: a zinc source, an aluminum source, an alkali source, and distilled water are transferred into a stainless steel reactor lined with polytetrafluoroethylene, heated at 300 to 500° C. for reaction for 24 to 72 hours, and cooled naturally to room temperature to obtain an aluminum oxide-zinc oxide precursor slurry, and the aluminum oxide-zinc oxide precursor slurry, yttrium salt, and peptizing agent are placed in a spray dryer for granulation to obtain a spherical aluminum oxide-zinc oxide precursor; the air inlet temperature of the spray dryer is 200 to 350° C., the fan frequency is 20 to 40 Hz, the needle passing time is 1 to 5 seconds, and the peristaltic pump speed is 10 to 30 r / min; (2) Preparation of spherical alumina-zinc oxide composite powder: The spherical alumina-zinc oxide precursor prepared in the above (1) is added to a crucible, and the crucible is then placed in a muffle furnace and calcined in air or oxygen at a calcination temperature of 800-1300°C for 1-12 hours. After the sintered body is naturally cooled to room temperature, it is placed in a planetary ball mill at a rotation speed of 100-300 r / min and ball-milled for 5-90 minutes to obtain spherical alumina-zinc oxide powder.
2. The method for preparing a spherical aluminum oxide-zinc oxide composite powder according to claim 1, characterized in that: In the step (1), the mass ratio of the zinc source, the aluminum source, the alkali source, the distilled water, the peptizing agent and the yttrium salt is 3-10:1-3:3-10:10-200:1-10:0.1-5.
3. The method for preparing a spherical aluminum oxide-zinc oxide composite powder according to claim 1, characterized in that: In the step (1), the zinc source is one or more of zinc chloride, zinc sulfate, zinc nitrate and zinc carbonate.
4. The method for preparing a spherical aluminum oxide-zinc oxide composite powder according to claim 1, characterized in that: The aluminum source in step (1) is one or more of aluminum chloride, aluminum nitrate, aluminum sulfate, sodium aluminum acid, and potassium aluminum acid.
5. The method for preparing a spherical aluminum oxide-zinc oxide composite powder according to claim 1, characterized in that: In the step (1), the alkali source is one or more of ammonia water, cyanuric chloride, melamine, urea and imidourea.
6. The method for preparing a spherical aluminum oxide-zinc oxide composite powder according to claim 1, characterized in that: In the step (1), the yttrium salt is one or more of yttrium chloride, yttrium nitrate, and yttrium acetate.
7. The method for preparing a spherical aluminum oxide-zinc oxide composite powder according to claim 1, characterized in that: In the step (1), the peptizing agent is one or more of acetic acid and citric acid.
Citation Information
Patent Citations
Preparation method of composite heat-conducting interface material heat-conducting silicone grease
CN112876849A
Preparation method of aluminum oxide filler and application of aluminum oxide filler in organic silicon two-component pouring sealant
CN118027709A
Preparation method of spherical aluminum-doped zinc oxide nanometer powder
CN101665237A
Aluminum-gallium co-doping zinc oxide nano-powder and preparation method for high intensity high conductivity sputtering coating target material thereof
CN103408062A
Preparation method of zinc oxide based nanometer composite powder resistance sheet
CN108329023A